2019
DOI: 10.1021/acsnano.9b05714
|View full text |Cite
|
Sign up to set email alerts
|

Engineering the In-Plane Structure of Metallic Phase Molybdenum Disulfide via Co and O Dopants toward Efficient Alkaline Hydrogen Evolution

Abstract: Molybdenum disulfide (MoS 2 ) has attracted much attention as a promising alternative to Pt-based catalysts for highly efficient hydrogen generation. However, it suffers sluggish kinetics for driving the hydrogen evolution reaction (HER) process because of inert basal planes, especially in alkaline solution. Here, we show a combination of heteroatom doping and phase transformation strategies to engineer the inplane structure of MoS 2 , that trigger their catalytic activities. Systematic characterizations are p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(38 citation statements)
references
References 44 publications
1
37
0
Order By: Relevance
“…This indicates that there is no phase change of the MoS 2 during the electrochemical cycling of the catalyst in alkaline conditions. A recent study has shown the presence of Co and O dopants in 1T−MoS 2 to improve the catalytic activity for the HER under alkaline conditions . This prior study however, used a heterostructure of 1T−MoS 2 with single walled carbon nanotubes to help improve charge transfer kinetics.…”
Section: Resultsmentioning
confidence: 99%
“…This indicates that there is no phase change of the MoS 2 during the electrochemical cycling of the catalyst in alkaline conditions. A recent study has shown the presence of Co and O dopants in 1T−MoS 2 to improve the catalytic activity for the HER under alkaline conditions . This prior study however, used a heterostructure of 1T−MoS 2 with single walled carbon nanotubes to help improve charge transfer kinetics.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, it can be seen that the intensity ratio of (002)/(103) of MoS 2 -PVP aerogels (7.3) is higher than that of MoS 2 (1.6), confirming that the PVP promotes the exfoliation of the MoS 2 nanosheets. 37,43 The morphologies of these samples are shown in Fig The FTIR spectra in Fig. 2c and d further indicate the interaction between MoS 2 and PVP.…”
Section: Introductionmentioning
confidence: 77%
“…36 Its unique structure advantages gives it great prospects in the fields of catalysis, batteries, and sensors. [37][38][39][40][41][42] Due to the extensive study of three-dimensional (3D) aerogels, the demand for MoS 2 aerogels is increasing to realize its potential application.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 3 b shows the Co K edge of the X‐ray absorption near‐edge structure (XANES) spectrum. Notably, compared with that of CoS 2 ‐com, the Co K edge of CoS 2 ‐1.5 h after the reaction shifted to a lower binding energy, which indicated that the valence state of Co became lower after the reaction [15] . This was because that Co 4+ /Co 3+ played the role of oxidizing .…”
Section: Figurementioning
confidence: 97%
“…Notably, compared with that of CoS 2 -com, the Co K edge of CoS 2 -1.5 h after the reaction shifted to a lower binding energy, which indicated that the valence state of Co became lower after the reaction. [15] This was because that Co 4+ /Co 3+ played the role of oxidizing CO 2 À to 1 O 2 in the reaction chain, and thus was reduced to Co 2+ with lower valence, which could also explain that in the high-resolution XPS spectrum of Co 2p, the peak area of Co 3+ did not increase significantly after a large amount of surface oxide layer dissolved out. Figure 3 c shows the Fe K edge of the XANES spectrum.…”
mentioning
confidence: 99%